HUBUNGAN INTERPESONAL DENGAN KEPUASAN KERJA PERAWAT DI RUANG ICU RSUD dr. HARYOTO LUMAJANG - Ike Prafita Sari; Nurul Mawaddah; Tri Retnaning Wulandari (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
One of the factors that influence nurse job satisfaction is the nurses' intrpersonal relationship with peers, patients and the surrounding environment. Nurses with high job satisfaction will improve their quality of life for the better. The method used in this research is correlational analytics. With a total sample of 30 respondents with a total sampling technique. The results showed that most respondents had good interpersonal relations of 24 respondents (80%). And most respondents had good job satisfaction as many as 23 respondents (76.70%). From the test results using the Spearman's rho test, the value of p <0.05 is p = 0,000 which means that there is an interpersonal relationship with the job satisfaction of nurses in ICU RSUD Dr. Haryoto Lumajang. With the better interpersonal relationships people are more open to express themselves, so the more effective the ongoing communication. As members of the nursing profession, nurses must be able to collaborate with colleagues to improve the quality of nursing services. Nurses must be able to foster good relations with all nurses in their work environment, Must respect each other and high tolerance so as to create job satisfaction in a hospital